2015
DOI: 10.1007/978-3-319-20609-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Learning Assistant System with Optical Head-Mounted Display (OHMD)

Abstract: Rapid increase in the use of wearable technologies, especially Optical Head-Mounted Display (OHMD) devices (e.g. Google Glass), suggests potentials for education and requires more scientific studies investigating such potentials. The issue of information access and delivery in classrooms can be of interest where multiple screens and objects of attention exist and can cause distraction, lack of focus and reduced efficiency. This study explores the usability of a single OHMD device, as an alternative to individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Du and Arya 39 conducted a study consisting of five scenarios involving 15 students to determine the effectiveness of learning simulation with an optical head-mounted display. This study observed that the students' cognitive load scores were low and there was no relationship between the scenarios and their cognitive load scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Du and Arya 39 conducted a study consisting of five scenarios involving 15 students to determine the effectiveness of learning simulation with an optical head-mounted display. This study observed that the students' cognitive load scores were low and there was no relationship between the scenarios and their cognitive load scores.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the students' sense of presence and cognitive load values after FDAC-VRT were measured in the experimental group, and the values were compatible with the literature. [39][40][41] It is assumed that the reasons for the low score on the scale are the excitement and curiosity of the students watching the fetal development with VR glasses for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 3D ISLs provide more real scenes as compared to 2D ISLs and users can achieve full immersion [157]. For achieving full immersion in 3D ISLs different technologies are used, such as HMD (Head Mounted Display) [158], CAVE (Cave Automatic Virtual Environment) [73] and Oculus VR Headsets [159]. Through these immersive technologies users can feel their physical presence and achieve fully-immersion in virtual environment.…”
Section: S No 2d Islsmentioning
confidence: 99%
“…The second indicated that the ability to evaluate at all stages along the development trajectory was key in the choice to adopt the 3-LEF [37]. And, the third paper indicated that the 3-LEF was selected because there were no other models specifically designed for wearable technology (a head-mounted display) [38].…”
Section: Reasons For Using the 3-lef Frameworkmentioning
confidence: 99%